The evolution of technology management practice in developing economies: findings from Northern China. (1st January 2002) - Walsh, Steven; Linton, Jonathan; Boylan, Robert; Sylla, Cheickna
In this paper, we present the results of a survey of Small and Medium Sized Enterprises, that all have foreign equity investors and are located in Northern China. Our findings are: that firms have changed their market focus from an export-oriented market to competing both locally and abroad; and that Wholly Foreign Owned Subsidiaries that serve export markets are shifting from a competitive advantage based on low cost labour to developing competitive advantage based on firm specific competencies.